The Development of ANTIC (Anti Bullying Cards) as a Medium for Introducing the Characteristics of Bullying in Criminal Act - Agung Aditya; Ariesma Setyarum; Huynh Thanh Tien; Cahya Wulandari; Suhadi Suhadi (Indonesian Journal of Advocacy and Legal Services, 2026)
Bullying in Indonesian schools remains a serious problem because it may involve conduct related to violence, threats, humiliation, defamation, cyberbullying, and social exclusion. At the elementary school level, students often still need concrete learning media to distinguish ordinary conflict or joking from bullying behavior that may carry social and legal consequences. This study aims to design ANTIC (Anti-Bullying Cards) as a card-based educational medium for introducing bullying as conduct with potential criminal law relevance to elementary school students. This research applies a Research and Development (R&D) approach using the ADDIE model, limited to the analysis and design stages. The needs analysis was conducted through behavioral observation, a homeroom teacher questionnaire, and literature review. The ANTIC model consists of 18 art-cartoon cards printed on 400 gsm material, covering threats, physical violence, verbal harassment, cyberbullying, rumors or defamation, and social exclusion. Each card presents visual illustrations, short explanations of social and psychological impacts, and simplified legal meanings related to Indonesian criminal law. The design was validated by three expert validators and one elementary school educator. The validation results showed that ANTIC was highly feasible, with an overall average feasibility score of 84.09%. Validators considered the media suitable for elementary school students, especially because of its visual form, age-appropriate presentation, and potential use in classroom discussion. This study concludes that ANTIC is feasible as a preliminary prototype for early criminal law literacy and preventive legal empowerment in school-based bullying prevention. Further research should test its effectiveness through classroom implementation and evaluation.